Childhood Experiences of Perpetrators of Child Sexual Abuse. Issue 3 (17th August 2012) - Thomas, Sandra P.; Phillips, Kenneth; Carlson, Kelly; Shieh, Elizabeth; Kirkwood, Elizabeth; Cabage, Linda; Worley, Julie
<x xml:space="preserve">Abstract</x> PURPOSE: This study explored the childhood experiences of perpetrators of child sexual abuse. DESIGN AND METHODS: A blend of narrative inquiry and phenomenology was employed. Interviews were conducted with 23 community‐dwelling perpetrators (21 males, 2 females). The education of participants ranged from GED to PhD. FINDINGS: There were four types of narratives: There Was No Love; Love Left; Love Was Conflated With Sex; and a Pretty Good Childhood. Chronic sorrow for a painful childhood was evident in most participants. PRACTICE IMPLICATIONS: Cognitive‐behavioral treatment may not be optimal for all perpetrators because it is not designed to facilitate recovery from early trauma and loss.